2019
DOI: 10.1093/eurheartj/ehz746.0119
|View full text |Cite
|
Sign up to set email alerts
|

6070Association of blood pressure measures with brain structure and function: the Southall and Brent REvisited (SABRE) study

Abstract: Background In our rapidly ageing society, dementia and neurocognitive decline are significant global public health problems. Blood pressure (BP), an established cardiovascular risk factor, has been extensively studied with respect to brain structure and function; however, findings across the literature differ depending on the BP component in consideration, and the use of brachial rather than central BP. Purpose We set out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…85 Besides, it is also recognized that pulse pressure is associated with brain structure and function, and suboptimal pulse pressure control may increase the risk of the development of cognitive impairment in elderly individuals. 86 Kannel et al, found that the incidence of cardiovascular events increased with a decrease in DBP <80 mmHg when the SBP remained ≥140 mmHg. 87 Besides, a study suggests that there is an interaction between DBP and CA in elderly patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Besides, it is also recognized that pulse pressure is associated with brain structure and function, and suboptimal pulse pressure control may increase the risk of the development of cognitive impairment in elderly individuals. 86 Kannel et al, found that the incidence of cardiovascular events increased with a decrease in DBP <80 mmHg when the SBP remained ≥140 mmHg. 87 Besides, a study suggests that there is an interaction between DBP and CA in elderly patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… 78,84 The 2018 European blood pressure guidelines affirmed that a pulse pressure >60 mmHg in older hypertensive persons increases the risk of cardiovascular disease 85 . Besides, it is also recognized that pulse pressure is associated with brain structure and function, and suboptimal pulse pressure control may increase the risk of the development of cognitive impairment in elderly individuals 86 . Kannel et al, found that the incidence of cardiovascular events increased with a decrease in DBP <80 mmHg when the SBP remained ≥140 mmHg 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maintaining optimal BMI levels predicted higher EF performance and sustained trajectories over time (Bohn et al, 2020). Regarding PP as a predictor, lower values of PP (indicating better vascular health in the form of reduced arterial stiffness) have beneficial effects such as preventing hypertension (e.g., mini-infarcts and cerebral vascular damage (Cooper et al, 2016), and reducing AD-related pathophysiology and other neurodegenerative processes (Nation et al, 2013; Warsch & Wright, 2010; Wong et al, 2019). Ultimately, better vascular health could promote positive EF effects with aging, such as the current retained complex structure and higher performance (Caballero et al, 2021; Mason et al, 2020; McFall et al, 2014).…”
Section: Discussionmentioning
confidence: 99%